High throughput phenotyping of root and shoot traits in Brassica to identify novel genetic loci for improved crop nutrition - Thomas, CL (2017)
Despite the success of breeding for high-yielding varieties during and since the ‘Green Revolution’, there are still an ever increasing number of people who suffer from malnutrition, due to both inadequate calorie intake and ‘hidden hunger’ from insufficient essential nutrients. There are also adverse impacts of such high-input, intensive agriculture on the wider environment. It is necessary therefore to focus breeding efforts on improving nutrient uptake and composition of crops, as well as improved yield. Roots have been an under-utilised focus of crop breeding, because of difficulty in observation and accurate measurement. Furthermore, genetic diversity in crop roots may have been lost in commercial varieties because of the focus on above-ground traits and the use of fertilisers. Techniques which can accurately measure phenotypic variation in roots, of a diverse range of germplasm at a high throughput, would increase the potential for identifying novel genetic loci related to improved nutrient uptake and composition.